2014
DOI: 10.1097/cmr.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Amuvatinib has cytotoxic effects against NRAS-mutant melanoma but not BRAF-mutant melanoma

Abstract: Effective targeted therapy strategies are still lacking for the 15–20% of melanoma patients whose melanomas are driven by oncogenic NRAS. We here report on the NRAS-specific behavior of amuvatinib, a kinase inhibitor with activity against c-KIT, Axl, PDGFRα and Rad51. An analysis of BRAF- and NRAS-mutant melanoma cell lines showed the NRAS-mutant cohort to be enriched for targets of amuvatinib, including Axl, c-KIT and the Axl ligand Gas6. Increasing concentrations of amuvatinib selectively inhibited the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Probably the most significant consequence of Axl upregulation in carcinomas of the skin is increased migratory ability of cells. In melanoma, Axl is associated with NRAS mutations compared to BRAF mutations, and is inversely correlated with the expression of the microphthalmia-associated transcription factor (MITF) [ 210 213 ]. Correlation studies also reveal the association of Axl with cell motility, invasion, and interactions with the surrounding microenvironment, and treatment with R428, a selective Axl inhibitor, reduces migration and invasion of cells [ 213 ].…”
Section: Tissue and Cell Type-specific Roles For Axlmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the most significant consequence of Axl upregulation in carcinomas of the skin is increased migratory ability of cells. In melanoma, Axl is associated with NRAS mutations compared to BRAF mutations, and is inversely correlated with the expression of the microphthalmia-associated transcription factor (MITF) [ 210 213 ]. Correlation studies also reveal the association of Axl with cell motility, invasion, and interactions with the surrounding microenvironment, and treatment with R428, a selective Axl inhibitor, reduces migration and invasion of cells [ 213 ].…”
Section: Tissue and Cell Type-specific Roles For Axlmentioning
confidence: 99%
“…Another report found that Axl and Mer are expressed in a mutually exclusive manner, where Mer is associated with BRAF mutations and Axl is associated with NRAS mutations [ 215 ]. Accordingly, treatment of NRAS-mutant melanoma cell lines with an inhibitor targeting multiple kinases including Axl, leads to growth arrest and apoptosis [ 210 ]. This drug has no effect in BRAS-mutant cell lines which lack Axl expression.…”
Section: Tissue and Cell Type-specific Roles For Axlmentioning
confidence: 99%
“…The exact compliment of RTKs responsible for driving innate or acquired resistance to small molecule kinase inhibitors in melanoma remains to be determined, and targeting these modalities remains a significant clinical challenge. Amuvatinib (MP-470), which inhibits MET, KIT, PDGFRA, and AXL, was shown to attenuate NRAS mutant melanoma cell growth and induce apoptosis in vitro [50]; however, MP-470 has not been assessed clinically. The small molecule MET, RET, KIT, FLT-1, FLT-3, FLT-4, TIE2, AXL, PDGFR-β kinase inhibitor XL-184 (cabozantinib) was assessed in a phase II randomized trial and demonstrated tumor regression in 55% of melanoma patients (5% objective response rate), with no correlation noted between response and BRAF status [51].…”
Section: Discussionmentioning
confidence: 99%
“…(46) Spheroids were treated with DMSO control or increasing concentrations of PF573228 for 72 hours, then stained with Calcein AM for viability at 30 minutes to 1 hour (Thermo Fisher, Waltham, MA), and imaged immediately.…”
Section: Methodsmentioning
confidence: 99%